(3bUI Gdchfs - (3LQjHjf, Lhfs; (3agej, eUWai EHQGgjes ((3GdbGgQIs (3cdeGJ YQHjI ddJQLeI h GdfTQs, 2013)
(3cja feG Gdchf ef cQI fGQjI eJfGgjI aj GdUZQ Edi MLeg GdMGdj ? h eG eUOQ GdMjGI Ydi GdCQV ? cja JfTC GdchGcH ? h eG eBdgG ? h ef Cjf dfG eYQaI Pdc cdg Ydi Cj MGd ? jQUO GdcGJH aj gPG GdcJGH JGQjN CYXe GdehVhYGJ Ydi GdEWdGb, h gh Gdchf faSg ef HOGjJg Edi fgGjJg (B( (3h eG hQGA Pdc (B). (3aJGQjN YGdefG HCcedg jeJO ef (B( (3GdEfaLGQ GdcHjQ (B) (3bHd (B14 (3edjGQ YGe, h eG CYbHg ef fTCI GdfLhe h GdeLQGJ h XghQ Chd CTcGd GdMjGI Ydi SWM GdchcH, Edi CMOK GdCacGQ Yf GdeGOI GdeXdeI h fXQjI cd TjF, h eG hQGA Pdc ef EMJeGd MOhK (B( (3GfSMGb cHjQ (B) (3Ch (B( (3JeRb cHjQ (B) (3aj GdeSJbHds
5 11 13
Keywords: (3Gdchfs; (3GdeLehYI GdTeSjIs